Police Union and Police Association Communications on Social Media and Legitimacy Spillover in Canada - Isaak, Nathan (International criminal justice review, 2022)
Although literature on police use of social media is expanding, almost all previous research has focused on police services. Existing literature has not examined the social media communications of multi-jurisdictional police unions and other associations. Unions represent police members during collective bargaining. Multi-jurisdictional police associations represent a specific issue or demographic within policing. We examine Twitter use by multi-jurisdictional police unions and associations in Canada. Although we demonstrate that there is variation by type of organization, we nevertheless contend the central aim of these union and associations communications is to provide horizontal legitimacy spillover, legitimizing not only police officers across Canada but the police institution itself. In conclusion, we reflect on what these findings mean for literatures on police social media communications and police unions and associations.